Student Management at the Anuban Sangkhom Islam Wittaya School, Sadao Songkhla Thailand - Muhammad Shaleh Assingkily (Yayasan Zia Salsabila, 2023)
This research aims to find out an overview of the implementation of student management at Anuban Sangkhom Islam Witaya School, Sadao Songkhla Thailand. This type of research is a qualitative descriptive research. Data collection techniques were carried out using structured interviews. The results of the research show that Anuban Sangkhom Islam Witaya School has met standards in student management, namely student planning is carried out by considering the number of students and the ratio between teachers and children, the presence and absence of students is recorded in the attendance book, student evaluation is carried out through several ways, namely observation and interviews. Implementation of the activities used are several methods, namely the